Technology Advancement Enabling the Link of Gut Microbiota with Obesity and Metabolic Disorder - Hatini Yusof,; Mohamad Shafiq Aazmi,; Ili Ng Abdullah,; Teh, Lay Kek; Aminuddin Ahmad,; Mazlifah Omar,; Thuhairah Rahman,; Mohd Zaki Salleh, (Penerbit UKM, 2015)
Obesity is a growing epidemic due to an accelerated phase of industrialization and urbanization with the overfed people now outnumbered the underfed. It is the major public health problem with a lot of research interest as it is associated with many complicated chronic disorders such as type-2 diabetes, cardiovascular diseases (CVD) and cancers. A global estimation of 2.8 million deaths per year is due to obesity and there are tremendous on-going efforts to identify hosts and environmental factors that infl uence the cause and pathogenesis of obesity. Concerted efforts from different research groups had successfully shown that obese subjects have altered composition of gut microbiota and transplantation of this microbiota infl uences body weight in the germ-free recipient mice. The advancement of technology had made possible the study of gut microbiota which was unculturable for better understanding of their impact to human health. Rapid deep sequencing of DNA at reasonable cost through various options of platforms followed by data analysis using robust bioinformatic tools are an important way of analysing the gut microbiome. Here we review the role of gut microbiota which modulates host’s metabolic functions and gene expression, facilitating the extraction and storage of energy from the ingested dietary substances and leading to body-weight gain. We will discuss on the different techniques used, focusing on the high-defi nition technologies for the determination of the composition, function and ecology of gut microbiota. This allows the appropriate selection of platform which becomes the key for success of subsequent research.